(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Background: Prolonged mobile device use may increase the risk of Carpal Tunnel Syndrome (CTS). This study explored the association between mobile usage patterns and CTS symptoms among college students. Methods: Two hundred students (115 females, 85 males; mean age = 20.31 ± 1.53 years) participated. Mobile use was assessed via questionnaire, and CTS symptoms using the Boston Carpal Tunnel Questionnaire, Phalen’s test, and Compression test. Results: Most (94%) used smartphones for 4–6 hours daily; 12% showed CTS symptoms. CTS was significantly associated with device type (p = 0.021) and longer screen time. Conclusion: Extended smartphone use was linked to higher CTS symptoms, emphasizing the need for awareness and preventive measures among students.